A Proposal for ASL Writing
The presenter discusses how American Sign Language can be written even though it incorporates space. He compares this to how two-dimensional maps are made of a three-dimensional world. He also provides reasons why video recordings are insufficient as "writing" for ASL -- for example, the benefits of acquiring a writing system in conjunction with your native language.